The Relationship Between Early Initiation of Breastfeeding (IMD) and the Prevention of Hypothermia in Newborns at the Tolangohula Community Health Center - Nely Usman Daud; Surya Indah Nurdin; Nou.r Arriza Dwi Me. lani; Yuliandari Yunus (Journal of Innovative and Creativity, 2025)
Hypothermia is one of the leading causes of neonatal mortality that still frequently occurs. Early Initiation of Breastfeeding (EIBF) is an effective effort proven to prevent heat loss in newborns through skin-to-skin contact between mother and baby. However, at Tolangohula Health Center, the implementation rate of EIBF remains low due to mothers’ lack of knowledge and limited environmental support. This study aimed to determine the relationship between EIBF and the prevention of hypothermia in newborns at Tolangohula Health Center. A quantitative research design with a cross-sectional approach was used, involving 45 postpartum mothers as respondents selected through total sampling. Data were collected through observation of EIBF implementation and measurement of newborns’ body temperature using a thermometer, and analyzed with the chi-square test. The results showed that 34 (75.6%) mothers performed appropriate EIBF, while 11 (24.4%) did not, and there was a significant relationship between EIBF implementation and the prevention of hypothermia in newborns (p < 0.05). It can be concluded that EIBF has a significant association with hypothermia prevention, and it is recommended that health workers be more proactive in providing education to pregnant women and families regarding the importance of EIBF to improve its implementation and reduce the risk of hypothermia and neonatal mortality.